A nanoparticle-functionalized wound dressing device for toxin neutralization. (March 2020) - Tao, Jie; Xu, Xin; Liu, Haofan; Jiang, Xian; Mao, Jian; Gou, Maling
Abstract: Pore-forming toxins (PFTs) that attack host cells have shown to perform an essential role in bacterial infections. Neutralization of these toxins has become an attractive approach to promote the recovery of damaged host tissues. In this study, we propose an interconnected macroporous hydrogel containing polydiacetylene (PDA) nanoparticles to efficiently sense and bind PFTs. The PDA nanoparticles are fabricated through a self-assembly process and then mixed into the gelatin monomer solution for polymerization. Using cryogelation technology, we can obtain the nanoparticle-functionalized hydrogels with controlled interconnected pores and well-defined properties. Meanwhile, the obtained hydrogels with favorable biocompatibility show the capability of retaining the nanoparticles over a long time and efficiently binding the PFTs. In addition, the functional hydrogels with different pores present distinctive detoxification abilities. Overall, this work introduces a promising detoxification device that incorporates functional nanoparticles into the macroporous hydrogel and could be used as a wound dressing for local treatment of bacterial infections in the future. Graphical abstract: Unlabelled Image Highlights: A wound dressing device consisted of polydiacetylene nanoparticles and gelatin hydrogel was prepared via cryogelation. The device with the ability to anchor polydiacetylene nanoparticles can neutralize pore-forming toxins for detoxification. The efficacy of this device to neutralize toxins can be readily controlled by the size of the macropores within the hydrogel.